2020
DOI: 10.7717/peerj.8571
|View full text |Cite
|
Sign up to set email alerts
|

Gynodioecy in the common spindle tree (Euonymus europaeusL.) involves differences in the asymmetry of corolla shapes between sexually differentiated flowers

Abstract: Gynodioecy is typically associated with a smaller perianth size in purely pistillate flowers than in hermaphrodite flowers. However, it is unclear whether this size differentiation is associated with any differences in flower shape between the two sexual groups. A geometric morphometric analysis of the symmetry of tetrameric corolla shapes was used in the study of Euonymus europaeus L., Darwin’s classical system of floral sexual differentiation. I investigated whether there are any shape differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Thus, it is likely that increased shape variation and DI of the zygomorphic female corollas, illustrated in this study, could be linked to this developmental pattern. Likewise, increased deviations from the radial symmetry of tetramerous actinomorphic corollas in the male-sterile flowers of gynodioecious E. europaeus also pointed to a similar developmental causation ( Neustupa 2020 ). Thus, it is possible that the decrease in corolla symmetry of the male-sterile flowers is a general pattern among angiosperms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Thus, it is likely that increased shape variation and DI of the zygomorphic female corollas, illustrated in this study, could be linked to this developmental pattern. Likewise, increased deviations from the radial symmetry of tetramerous actinomorphic corollas in the male-sterile flowers of gynodioecious E. europaeus also pointed to a similar developmental causation ( Neustupa 2020 ). Thus, it is possible that the decrease in corolla symmetry of the male-sterile flowers is a general pattern among angiosperms.…”
Section: Discussionmentioning
confidence: 89%
“…Our hypothesis was that corollas of female flowers might have increased DI due to lower selective pressure for their morphological symmetry and possible developmental perturbations caused by stamen abortion. Recently, it was shown that the position and shape of petals composing the corolla of female flowers in gynodioecious Euonymus europaeus were more asymmetric than their hermaphroditic counterparts ( Neustupa 2020 ). However, in their purely actinomorphic flowers, typical of radial symmetry lacking any adaxial–abaxial differentiation, it was not possible to differentiate between possible directional asymmetry (DA) and FA of their corolla shapes.…”
Section: Introductionmentioning
confidence: 99%
“…This study is unusual because the orientations of all flowers were recorded. This is done very rarely for compass orientation (Tucić et al, 2018), but it is not always feasible even for the anatomical position, for instance in actinomorphic flowers when no clear markers of adaxial–abaxial orientations are available (e.g., Frey et al, 2007; Neustupa, 2020). In such a situation, it is impossible to separate directional and fluctuating asymmetry and analyses, therefore, need to consider a single component of total asymmetry (Klingenberg, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation, it is impossible to separate directional and fluctuating asymmetry and analyses, therefore, need to consider a single component of total asymmetry (Klingenberg, 2015). This overall measure of asymmetry, sometimes called “radial asymmetry,” is usually treated like fluctuating asymmetry and used as a measure of developmental instability (e.g., Frey & Bukoski, 2014; Neustupa, 2020; Perfectti & Camacho, 1999; Siikamäki & Lammi, 1998; Tucić et al, 2008). This is not a serious problem in practice if directional asymmetry is only a minor proportion of total asymmetry, but of course, it complicates the interpretation of the results (Palmer & Strobeck, 2003; Tucić et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2B), where the parts are attached to each other in a fixed arrangement (such as the left and right halves of our face, where the plane of symmetry runs through the middle of the face) [30,31]. In some instances, investigators have a choice between these types of symmetry [27]: in flowers, for instance, a study might investigate the object symmetry of the whole flower [32,33], or it might focus on the variation among the different petals separately and use the method for matching symmetry [24,34]. In addition, the parts of a structure with complex symmetry may each be symmetric in themselves, for instance if the parts of a complex structure each have bilateral object symmetry [24,27,[34][35][36].…”
Section: Quantifying Shape Variation and Asymmetrymentioning
confidence: 99%